2010
DOI: 10.1165/rcmb.2008-0397oc
|View full text |Cite
|
Sign up to set email alerts
|

Flt3-L Increases CD4+CD25+Foxp3+ICOS+Cells in the Lungs of Cockroach-Sensitized and -Challenged Mice

Abstract: We previously reported in an ovalbumin-induced model of allergic asthma that Fms-like tyrosine kinase 3 ligand (Flt3-L) reversed airway hyperresponsiveness (AHR) and airway inflammation, and increased the number of regulatory CD11c high CD8a high CD11b low dendritic cells in the lung. In this study, we investigated the effect of Flt3-L in a clinically relevant aeroallergen-induced asthma on the phenotypic expression of lung T cells. Balb/c mice were sensitized and challenged with cockroach antigen (CRA), and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
0
21
1
Order By: Relevance
“…In addition, we found that ovalbumin-sensitized mice treated with Flt3-L increased the number of regulatory CD11c high CD8a high CD11b low DCs in the lung (42). We also found that administration of Flt3-L significantly increased the number of CD4 1 CD25 1 Foxp3 1 IL-10 1 T cells in the lungs of cockroach-sensitized and -challenged mice (43). Furthermore, adoptive transfer of T-regulatory cells (Tregs) reverses AHR and airway inflammation (45).…”
mentioning
confidence: 54%
“…In addition, we found that ovalbumin-sensitized mice treated with Flt3-L increased the number of regulatory CD11c high CD8a high CD11b low DCs in the lung (42). We also found that administration of Flt3-L significantly increased the number of CD4 1 CD25 1 Foxp3 1 IL-10 1 T cells in the lungs of cockroach-sensitized and -challenged mice (43). Furthermore, adoptive transfer of T-regulatory cells (Tregs) reverses AHR and airway inflammation (45).…”
mentioning
confidence: 54%
“…The therapeutic effect of Flt3L is not only limited to the OVAinduced mouse model of allergic airway inflammation, but it has been observed in a clinically relevant cockroach-induced mouse model of asthma (29). Our study helps define the role of Th1 activation in counteracting Th2 response in allergic asthma.…”
Section: Discussionmentioning
confidence: 80%
“…On Days 28-30 and Day 32, mice received an aerosol challenge of CRA antigen (50 mg/ml). On Day 33, AHR to methacholine was measured according to the established methods in our laboratory (24,25) (Figure 1). …”
Section: Induction Of Ahr By Sensitization and Challenge With Cramentioning
confidence: 99%
“…Mice were mechanically ventilated with Harvard Rodent Ventilator model 683 (Harvard Apparatus, Holliston, MA). Mice were challenged with aerosolized PBS, followed by increasing doses of methacholine (3.1, 6.25, 12.5, 25, 50, and 100 mg/ml) to measure specific airway resistance (24,25).…”
Section: Assessment Of Specific Airway Resistancementioning
confidence: 99%
See 1 more Smart Citation